Roger Bacon’s Ars poetica sacra: Spiritual Persuasion and the Christian Sublime (Itinera, 2024)
Roger Bacon (d. ca. 1292) wrote extensively on rhetoric and poetics. He did so in the context of a critical overview of the religious culture of his age. He places poetry (the argumentum poeticum) at the very pinnacle of culture, above the sciences, above the liturgy and preaching, well above scholastic philosophy and any other mode of expression current in his age. Poetry and rhetoric are the modes of exposition capable of captivating and transporting the listener/reader. That makes them an effective means of converting and of inspiring faith. The religious culture of his own time has so far declined that it is incapable of performing this function. Bacon was looking back on real rhetorical practices that had become outmoded. In earlier days Christianity spoke with force and passion. His sacred poetics has a place in the history of pre-modern Christian discourse, one of two works theorizing sacra eloquentia; the other is Augustine’s On Christian Doctrine. Christian traditions of teaching, preaching, prayer, oratory, sacred music, regularly had called on modes that were emphatic, forceful and passionate: the “grand style,” sermo propheticus, sermo affectuosus. Bacon’s poetics commends these modes as it laments their passing.
Keywords: rhetoric, poetics, sacra eloquentia, grand style, spiritual persuasion